Turkey : Eighth Review Under the Stand-By Arrangement-Staff Report; Staff Statement; and News Brief on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2001)
The momentum in economic reform and disinflation has been maintained by Turkey under the Stand-By Arrangement (SBA). Executive Directors commended the financial sector reform, the achievements in restructuring the economy and improving its economic fundamentals, and emphasized the need to accelerate structural reforms, restructure the state banks and intervened private banks, improve money market stability, and enhance governance and fiscal transparency. They commended the strong and comprehensive efforts to implement their strengthened program and approved the completion of the eighth review under the SBA.